Irrigation And Risk Of Saline Pollution. Example: Groundwater Of Annaba Plain (North East Of Algeria) - Samia, Halimi; Fethi, Baali; Nacer, Kherici; El moncef, Zairi; Saad, Bouhsina (European Scientific Journal, ESJ, 2016)
In the Annaba plain (Northeast of Algeria), the anthropogenic activities have imposed serious unfavorable impacts on hydraulic, hydrochemical and biological balances that influence the socio-economic future of this area. A hydrochemical analysis was performed in 29 wells distributed over the whole of the plain region during the period of high water (December 2013) to assess the quality of groundwater for its suitability for irrigation. Several parameters were analyzed such as pH, TDS, Ca +2, Mg +2, Na+ , K+ , HCO3 - , Cl- and SO4 - . Analysis of results suggests that groundwater in the study area has the same qualities; however the observed degradation reflects a change in the water quality, and the SAR values vary from 0.08 to 16 with an average of 1.3. The US salinity laboratory, Wilcox, and percentage Na+ it suggest that the majority of groundwater samples are not good for irrigation.